Two superhelix density-dependent DNA transitions detected by changes in DNA adsorption/desorption behavior - Fojta, M; Bowater, R P; Stanková, V; Havran, L; Lilley, D M; Palecek, E (Biochemistry, 1998)
The adsorption behavior of covalently closed circular plasmid DNA at the mercury/water interface was studied by means of AC impedance measurements. The dependence of the differential capacitance (C) of the electrode double layer on the potential (E) was measured in the presence of adsorbed DNA. It was found that the C-E curves of supercoiled DNA at native and highly negative superhelix densities (sigma), relaxed covalently closed circular DNA, and nicked DNA differed from each other. A detailed study of topoisomer distributions ranging from -sigma of 0 to 0.11 revealed two supercoiling-dependent transitions, at about -sigma = 0.04 (transition TI) and 0.07 (transition TII). Transition TI was detected by measuring the height of the adsorption/desorption peak 1 (at about -1.2 V against the saturated calomel electrode) and the decrease of capacitance (DeltaC) at -0.35 V. This transition may be due to a sudden change in the ability of the DNA to respond to the alternating voltage, probably caused by changes in the DNA tertiary and/or secondary structure. Transition TII was detected by measuring peak 3* (at about -1.3 V), which was absent in topoisomers with -sigma less than 0.05. This transition is due to changes in the DNA adsorption/desorption behavior related to increased accessibility of bases at elevated negative superhelix density. Opening of the duplex at highly negative superhelix density was also detected by the single-strand selective probe of DNA structure, osmium tetroxide, 2, 2'-bipyridine. Our results suggest that electrochemical techniques provide sensitive experimental analysis of changes in DNA structure.
Keywords: plazmidy; hydrolýza; Plasmids; konformace nukleové kyseliny; Nucleic Acid Conformation; Adsorption; elektrochemie; DNA, Superhelical; Electrochemistry; superhelikální DNA; Single-Strand Specific DNA and RNA Endonucleases; Hydrolysis; endonukleasy specifické pro jednořetězcové nukleové kyseliny; adsorpce